Unmasking GluN1/GluN3A excitatory glycine NMDA receptors - Teddy Grand (Nature Portfolio, 2018)
Excitatory glycine GluN1/GluN3A receptors are atypical NMDARs that have been difficult to study. Here the authors identify new properties of these receptors, including potentiation by the GluN1 antagonist CGP-78608 that allows detection of functional GluN1/GluN3A receptors in the juvenile brain.